Dialogic pedagogy in the supervision of social studies student teachers. Issue 1 (21st May 2018) - Cuenca, Alexander
Abstract : Purpose: Research reveals very little about how the supervision of social studies student teachers ought to be enacted. The paper aims to discuss this issue. Design/methodology/approach: Based on the broader arguments for the democratic purposes of social studies, the author argues for the development of the democratic capacities of teacher citizens by creating deliberative and dialogic spaces in social studies field-based teacher education. Findings: Four conceptual dimensions of dialogic pedagogy in the supervision of social studies student teachers are explored: questioning, listening, negotiation, and self-critique. Originality/value: Because supervision of student teachers is a pedagogical interaction, a pedagogy of social studies field-based teacher education must be grounded in dialogue and deliberation.